Um estudo das questões da obmep sobre análise combinatória - Silva, Francisco Felipe Gomes da (2020)
This work has the objective of forming a self-sufficient material for primary school teachers to work, through problem solving and counting topics. Initially, a whole overview of the Brazilian Public Schools Math Olympics – OBMEP - is presented, showing some of its main programs, private/ local student results and national awards for 2019. We show that the problem solving as a pedagogical practice plays an importante role for the teaching of math, and that from it we managed to attract the student’s attention to the most diverse mathematical challenges. We also have a chapter where all the questions about combinatorial analysis of the first phase of level 3 of the OBMEP are presented, showing all the official solutions available on the program website and, whenever possible, an alternative solution, with paths and steps to be followed. For each of these problems, a small script for teacher is prepared with tips for solving, suggestions for simpler problems and related to the one presented. All the content needed to resolve the issues is also exposed in Chapter 3 of this dissertation, thus forming material that will serve as a basis for teachers of basic education, focusing on high school